BASED PROJECT LEARNING BASED AKTIVITIES ON ENVIRONMENTAL AWARENESS - Sri Hanipah; Ni Nyoman Rediani; Fanny Gustini; Suprianton Walokau (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The suboptimal environmental awareness among students is one of the reasons for the environmental issues faced by society. To improve this, proper learning is needed that fosters environmental care attitudes. This is the reason why research aimed at examining the effect of activity-based project-based learning on environmental care attitudes was conducted. This type of research uses a pseudo-experimental method with a posttest-only control group design. The research subjects were fifth grade students, and the data collection methods were observation, interview, and questionnaire. The results of the t test showed that the activity-based PjBL model had a positive influence on students' environmental care attitudes. This finding is supported by the significance value (Sig.), which is less than 0.05, namely 0.00. Therefore, it is recommended that this learning model be considered as a potential solution to enhance students' environmental awareness and address the suboptimal state of environmental consciousness.